PENGEMBANGAN DESAIN DIDAKTIS GEOMETRI BERBANTUAN PERANGKAT LUNAK CABRI3D PADA PEMBELAJARAN MATEMATIKA SMA - Arif Abdul Haqq (Jurnal THEOREMS (The Original Research of Mathematics), 2020)
This research is motivated by the difficulty of students to learn the geometry of 3rd dimension, especially on the concept of distance so that it is felt that there is a need for virtual media props in the form of Cabri3D software. This virtual teaching aid is used as an alternative stimulus to the design of mathematics learning in the geometry of the 3rd  dimensional concept of distance. This design was designed with great attention to the characteristics of the phenomenon of learning obstacle and learning trajectory. The research was conducted at SMA Negeri 5 Kota Cirebon for class XII as many as 93 people. The research method used is qualitative research with Didactical Design Research. The results of this study are the character of the phenomenon of learning obstacle and learning trajectory on Geometry of 3rd Dimension concepts Distance Concept and didactical situation analysis as the design of the material.ABSTRAKPenelitian ini dilatarbelakangi oleh sulitnya siswa untuk mempelajari geometri dimensi 3 khususnya pada konsep jarak sehingga dirasa perlu ada media alat peraga maya berupa perangkat lunak Cabri3D. Alat peraga maya ini digunakan sebagai stimulus alternatif desain pembelajaran matematika pada materi geometri dimensi 3 konsep jarak. Desain ini dirancang dengan sangat memperhatikan karakteristik fenomena learning obstacle dan learning trajectory. Penelitian ini dilakukan di SMA Negeri 5 Kota Cirebon terhadap kelas XII sebanyak 93 orang. Metode penelitian yang digunakan adalah penelitian kualitatif dengan Didactical Design Research. Hasil penelitian ini adalah karakter fenomena learning obstacle dan learning trajectory pada materi Geometri Dimensi 3 Konsep Jarak serta analisis situasi didaktis sebagai desain materinya.